Cloud Storage Data Protection Mechanism Based on a Fingerprint Cube Algorithm - Hao Wu; Jiulun Fan; Jianhua Liu; Junsheng Zhang (Dianxin kexue)
Cloud storage is an effective solution to the storage performance bottleneck, but it also gives rise to problems of data security and privacy protection. In order to solve this problem, a cloud storage data protection mechanism based on a fingerprint cube algorithm was developed. Mechanism through the user's fingerprint characteristic value control cube rotation to encrypt files, and then use threshold segmentation technique to split the file into small blocks to each storage server. If it is expected to restore the original file, check the integrity of each block at first, and then find no less than the threshold number of file blocks, which leads to recover the full document. The mechanism protects the privacy of user data stored in the cloud, but also improve the anti-destruction capability and flexibility of cloud storage system.